Evaluating the Independent Neighborhood Association Program: Success, Challenges, and Economic Implications in Banjarbaru City, South Kalimantan - Purboningsih, Dewi; Anjani, Anjani; Azis, Nana Abdul (Journal Public Policy, 2024)
The Independent Neighborhood Association Program is a premier initiative of the Banjarbaru City Head aimed at fostering, mobilising, and promoting community engagement in development and empowerment activities at the Urban Village level, centred on Neighborhood areas. This study is the purpose of the success or failure of policy implementation in the Neighborhood Independent Program. The research employed a qualitative methodology utilising the Edward III Implementation Model for analysis, which evaluates policy success through the dimensions of resources, communication, disposition, and organisational structure. The study's findings indicated that the Independent Neighborhood Association Program, aimed at enhancing the economy of Banjarbaru City, successfully met one of its objectives by mobilising and motivating community participation in regional development activities. However, the enhancement of community welfare remains unobserved, as most POKMAS are still in the implementation phase and have yet to contribute significantly to the community's economic value. The examination of the elements affecting the execution of the Independent Neighborhood Association Program has satisfied four criteria. This encompasses the program's communication, particularly the presence of ongoing Urban Village deliberation; the resource dimension, involving BAPPEDA, the Urban Village head and POKMAS, has successfully executed its responsibilities; the disposition aspect, or the attitude of the implementers of the Independent Neighborhood Association Program, specifically the community group, has effectively conducted business activities, yet a significant challenge persists, hindering progress. POKMAS has the challenge of marketing agriculture. The government structure has been established, with tasks allocated and a method for execution outlined by the SOP for this program.